Translation Strategies of Nusantara Food Menu - Pratama, Agus Darma Yoga; Putri, Dewa Ayu Dyah Pertiwi (MOZAIK HUMANIORA, 2024)
The research aims to analyze the translation strategies and the use of Culture-Specific Items (CSIs) in nusantara food menus in Indonesia. Translators usually use their perception to translate the menu without the involvement of the chefs. As a result, the translation of food menus can vary from one restaurant to another because each chef has their unique way of preparing their food. Collaboration between translators and chefs is necessary to ensure that the translated menus highlight the characteristics and uniqueness of each dish. The results show that the translation strategies used are Reduction and Expansion (81 data), Couplets (34 data), Cultural Equivalence (8 data), Transference (7 data), Descriptive Equivalence (5 data), Functional Equivalence (4 data), and Naturalization (2 data). The use of CSIs found in the data are Ingredients (186 data), Cooking Techniques (113 data), Seasoning (83 data), Proper Name (39 data), Flavor (9 data), Color (7 data), and Texture (4 data). However, the translation strategy of Synonymy, Through-Translation, Shift or Transposition, Modulation, Recognised Translation, Translation Label, Compensation, Componential Analysis, Paraphrase, and Other Procedures are not found in the data.